The role of deposit insurance and bank’s asset size in the 2008 financial crisis - Kanji, Hetal Rajesh (2014)
In this paper we analyze the role of deposit insurance in providing the market with liquidity in times of financial turmoil. To do so, we look at the variation in insured and uninsured deposits between 2005Q3 and 2011Q3, controlling for liquidity, solvency and capital adequacy indicators, and find evidence that deposit insurance does provide some confidence in keeping funds in banks in times of turmoil. Additionally we follow an event study methodology to assess the impact of deposit insurance oriented policies on bank holding companies stock market returns, and find a TBTF effect.